1992
DOI: 10.1093/bja/68.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Requirements for the Management of War Injured: The Experience of the International Committee of the Red Cross

Abstract: The quantity of blood required in the total surgical care of 4470 war injured patients in four hospitals was 44.9 units for every 100 patients admitted (u/cp). Patients evacuated to hospital in less than 6 h from wounding required 59.8 u/cp; patients admitted as a result of antipersonnel mines required 103.2 u/cp. Patients with burns potentially require most blood. Whether these figures permit prediction of transfusion requirements for future conflicts is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…For those wounded who would die on the early steep part of the survival curve surgery is effective only when access to them is rapid, when resuscitation, postoperative care, hospital organisation, specialised surgical skill, resources, and time are adequate, and when blood transfusion is safe 33. The small proportion of patients who benefit from urgent surgery must not divert attention and resources from the majority who still require surgery for survival but less urgently or from those who require surgery for improved quality of survival.…”
Section: Discussionmentioning
confidence: 99%
“…For those wounded who would die on the early steep part of the survival curve surgery is effective only when access to them is rapid, when resuscitation, postoperative care, hospital organisation, specialised surgical skill, resources, and time are adequate, and when blood transfusion is safe 33. The small proportion of patients who benefit from urgent surgery must not divert attention and resources from the majority who still require surgery for survival but less urgently or from those who require surgery for improved quality of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Three or more surgical procedures were chosen because a study with 16 172 patients treated at ICRC's hospitals demonstrated that 66% of the patients were treated with two surgical procedures or fewer [4]. Three or more blood transfusions was chosen as a measure because a previous ICRC-study with 4470 weapon-injured patients demonstrated that 15.5% were transfused and an average of 2.9 units was given [20]. Furthermore, the ICRC recommends an availability of 100 units/100 patients if anti-personnel mines are used in the conflict [4].…”
Section: Methodsmentioning
confidence: 99%
“…The use of intravenous crystalloid or colloid in treating landmine injuries is also controversial. Although volume replacement in the profoundly shocked patient is necessary, overemphasis on vigorous fluid resuscitation can have deleterious effects, as well as create an unnecessary logistic strain [6]. We recommend using intravenous fluid primarily to maintain intravenous access for drug administration.…”
Section: Treating Type 1 Landmine Injuriesmentioning
confidence: 99%